No Long-Term Benefit of Candesartan for Patients with Acute Stroke - Rizzo, Toni (MD Conference Express, 2014)
Elevated blood pressure (BP) in the acute phase of stroke has been associated with poor short- and long-term outcomes [Leonard-Bee J et al. Stroke 2002]. The Scandinavian Candesartan Acute Stroke Trial [SCAST; NCT00120003] did not demonstrate a difference at 6 months between BP lowering with candesartan and placebo for 7 days in the acute phase of stroke (HR, 1.09; 95% CI, 0.84 to 1.41; p=0.52) [Sandset EC et al. Lancet 2011]. The aim of this SCAST prespecified secondary analysis was to investigate whether a difference might be observed over longer follow-up.